2020
DOI: 10.21307/ane-2019-035
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and environmental enrichment: Behavioural effects of exposure to different housing conditions in mice

Abstract: Enriched environments and exercise provide complex environmental stimulation that can induce emotional and cognitive changes; however, few studies have evaluated the effects of these two components on other behaviours, such as novelty seeking or pain sensitivity. The aim of the present study was to investigate the influence of voluntary physical activity provided through different housing conditions on anxiety, locomotor activity, pain sensitivity, and exploration. Male mice at postnatal day (PND) 21 and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Multiple studies have investigated the effects of environmental enrichment on anxiety using the elevated zero maze in mice 31 35 . Unlike the consistent findings that environmental enrichment attenuates novelty reactivity, the effects of environment enrichment on anxiety have been less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have investigated the effects of environmental enrichment on anxiety using the elevated zero maze in mice 31 35 . Unlike the consistent findings that environmental enrichment attenuates novelty reactivity, the effects of environment enrichment on anxiety have been less clear.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that, in the tested strains and under the experimental conditions used in the present study, sex but not housing condition interacts with strain to influence anxiety. www.nature.com/scientificreports/ Multiple studies have investigated the effects of environmental enrichment on anxiety using the elevated zero maze in mice [31][32][33][34][35] . Unlike the consistent findings that environmental enrichment attenuates novelty reactivity, the effects of environment enrichment on anxiety have been less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our EE animals showed enhanced sensitivity to sensory input and enhanced prepulse inhibition. Regarding the effect of EE on sensory function, a limited number of previous studies reported inconsistent results among different strains (Abramov et al, 2008; Chen et al, 2010; Rabadán et al, 2019; Varty et al, 2000). The present study provides further insights into the impact of environmental factors on animal physiology and behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies conclude that the use of EE is beneficial for the animals. Housing in enriched environments can reduce stereotypies (3)(4)(5)(6)(7), reduce anxiety (8)(9)(10) and promote exploratory behavior (11,12), as well as promote the development of favorable physiological parameters, especially in the neurological field (13,14). It is also important that the enrichment is versatile and easily accessible.…”
Section: Introductionmentioning
confidence: 99%